Implementasi Metode Keteladanan dalam Meningkatkan Moral Anak Usia Dini - Nayyiroh; Rachmy Diana (Institut Agama Islam Negeri Madura, 2022)
Early childhood is a child whose age range is 0-6 years, this period is the right time to provide a good stimulus for children for their intelligence, development and morals. Moral is very important given to children because morals are what determine a person's good and bad. In improving morale, of course, teachers use methods, one of which is the exemplary method, namely by presenting direct examples to children. In this study using qualitative descriptive, while the data sources were obtained through the process of interviews, observation and retrieval of documentation. The informant is the teacher as an exemplary figure. While the validity of the data is checked by adding participation. The researchers from the results of this study indicate that: First, the implementation of the exemplary method in improving morale is done by imitating good things, namely by praying in congregation, praying, throwing trash when needed, being weak to others. Second, the result of the application of exemplary application makes children automatically perform without even a single moment, for example, being able to perform ablution by themselves, throwing garbage in its place, and speaking well for hours together.